2008
DOI: 10.1002/ptr.2725
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiinflammatory effect of Epilobium parviflorum Schreb.

Abstract: Epilobium parviflorum Schreb. (Onagraceae) is used for the treatment of benign prostatic hyperplasia (BPH), but its biological action is not entirely identified. This paper aims to report data on E. parviflorum with respect to its antioxidant and antiinflammatory effects. The aqueous acetone extract of E. parviflorum showed higher antioxidant effect in the DPPH assay than well known antioxidants and inhibited the lipid peroxidation determined by the TBA assay (IC(50) = 2.37 +/- 0.12 mg/mL). In concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Moreover, a single fraction HF 11–14b showed significant anti-inflammatory activity. Diverse studies have demonstrated that different members of the Onagraceae family have selective anti-inflammatory activity in animal models [7, 8, 15, 27] and cytotoxic activities against several tumor cell lines [11, 12, 2830]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a single fraction HF 11–14b showed significant anti-inflammatory activity. Diverse studies have demonstrated that different members of the Onagraceae family have selective anti-inflammatory activity in animal models [7, 8, 15, 27] and cytotoxic activities against several tumor cell lines [11, 12, 2830]. …”
Section: Discussionmentioning
confidence: 99%
“…Among flavonoids, isolated compounds from this family include flavonols, glycoflavones, flavones, and chalcones [13, 14]. Most of the genera studied possess mainly flavonols, which include myricetin, quercetin, kaempferol, and remarkable amounts of various phenolic acids [6, 7, 15]. Furthermore, some species produce significant amount of tocopherols, compounds that have been used as chemotaxonomic markers within the Onagraceae family [16].…”
Section: Introductionmentioning
confidence: 99%
“…Active compounds have not been identified (Hiermann, Juan, & Sametz, ; Juan, Sametz, & Hiermann, ). Either ethanolic or aqueous acetone extract of E. parviflorum has inhibited in vitro COX‐1 and COX‐2 enzymes, involved in the prostaglandin biosynthesis (Hevesi et al, ; Steenkamp, Gouws, Gulumian, Elgorashi, & van Staden, ), decreasing prostaglandin E 2 release (Hevesi et al, ). Furthermore, its dichloromethane extract has demonstrated a moderate inhibition of NF‐kB (Vogl et al, ).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…[23][24][25] Various herbal extracts reduce oxidative stress in testosterone-induced BPH rats. [26][27][28][29] In addition, saw palmetto extract, which is commonly used to treat BPH, has shown antioxidant effects. 30 Therefore, antioxidants can be considered good candidates to suppress the development of BPH.…”
mentioning
confidence: 99%